2018
DOI: 10.5812/ijpbs.9697
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability and Efficacy of Transdiagnostic Cognitive Behavior Therapy on Reducing Signs and Symptoms of Borderline Personality Disorder With Co-Occurring Emotional Disorders: A Pilot Study

Abstract: Background: Borderline personality disorder (BPD), which is highlighted by emotional dysregulation and high rates of comorbid emotional disorders, is one of the most challenging clinical conditions for mental health services in different communities. The Unified protocol for the transdiagnostic treatment of emotional disorders (UP) was designed to target common vulnerabilities across emotional co-occurring disorders. Objectives: The aim of the present study was to examine the preliminary efficacy of the UP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…For limitations, many identified small samples sizes [19,20,23,[26][27][28] and durations of follow-up [22,23,26,29], lack of randomization, lack of a control group, or study methodology was identified as a limitation in three of the studies [20,22,30]. Three studies mentioned their lack of long-term follow up as a limitation [31][32][33] The treatment group had lower scores on the BPDSI and 3 subscales of the GHQ-28, and higher scores on 5 subscales of the PRQC one month after the end of treatment.…”
Section: Adverse Effects Acceptability Suicidal Ideationmentioning
confidence: 99%
See 1 more Smart Citation
“…For limitations, many identified small samples sizes [19,20,23,[26][27][28] and durations of follow-up [22,23,26,29], lack of randomization, lack of a control group, or study methodology was identified as a limitation in three of the studies [20,22,30]. Three studies mentioned their lack of long-term follow up as a limitation [31][32][33] The treatment group had lower scores on the BPDSI and 3 subscales of the GHQ-28, and higher scores on 5 subscales of the PRQC one month after the end of treatment.…”
Section: Adverse Effects Acceptability Suicidal Ideationmentioning
confidence: 99%
“…DBT and schema therapy, they had no female participants [26]. Multiple studies reported limited generalizability of the sample population, with Orduna et al explaining that their sample was a highly motivated group, which is less generalizable to the greater personality disorder population [19,33]. Although self-report scales were the primary outcome measures in most studies, only one study acknowledged this as a limitation [34].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…En su metaanálisis, Aldao et al (2010) evidencian que en personas con problemas de ansiedad y depresión existe un déficit común en las estrategias de regulación de emociones negativas (como la aceptación, la reevaluación y la solución de problemas). Más allá de los trastornos relacionados con la ansiedad y la depresión, existen propuestas para añadir otros trastornos que presentan similitudes con los trastornos emocionales, como el trastorno límite de personalidad (Mohammadi et al, 2018) y el trastorno de estrés postraumático (O'Donnell et al, 2021).…”
Section: Introductionunclassified